Soil science simplified - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Tropical soils and fertilizer use by P M Ahn 1992 264pp ISBN 0 582 77507 8 Pbk Price UKL8.95 Longman international Education Longman House, Burnt Mill, Harlow Essex CM20 2JE, UK